PEMBERDAYAAN MASYARAKAT DALAM PRODUKSI IKAN LELE MENGGUNAKAN MAGGOT DAN MANAJEMEN BUDIDAYA PADA KELOMPOK PERIKANAN DI DESA SUKARAJA - Ewin Handoco; Gunaria Siagian; Ria Retno (Nusantara Hasana Journal, 2025)
The people living in the Sukaraja Village area are farmers, fish farmers and traders. The partner problem is that the fish farming community in Sukaraja Village still relies on factory-made feed, causing the price of the feed product to be very high, reaching 70% of the total production cost. The community partnership empowerment program supports the community to improve production and business management that has been carried out, so that the group community can increase income and capacity and be sustainable for their business, through education, training and mentoring as well as program evaluation. The community partnership empowerment activity for productive economic partners, namely the fish farming group, namely Setia Farm, is carried out in 5 stages in implementing the offered solutions concerning problems in the fields of production and management. This community partnership empowerment activity uses a method of implementation stages, namely socialization, training, technology application, mentoring and evaluation as well as program sustainability. The target output of the solutions offered in the community partnership empowerment program is an increase in partner knowledge and skills, an increase in the level of partner empowerment quantitatively, namely an increase in income of 30% and production by 30%, the national journal sinta 5, modules, posters, videos, electronic mass media and copyright. The results obtained after the activity were an average of 100% increase in knowledge and 91% in partner management skills, existing posters, published electronic mass media.